Transformasi Etno-Musik Tradisional Sasak: Evolusi Budaya dan Pertentangan Kelas - Ramdhani, Ahmad Hadi (ASANKA : Journal of Social Science and Education, 2021)
This article tries to explain the phenomenon of the transformation of Sasak Ethno-music, namely Gendang Beleq as a high culture , dealing with Kecimol as a pop culture in sasak community. Both types of music have developed in contemporary Sasak society with contrasting nuances. The first one represents the musical taste of the Purwangse (aristocracy) group, while the second represents the Jajar Karang group. Furthermore, Gendang Beleq claimed to be a pure culture, while Kecimol  stigmatized as a splinter culture.This study uses a qualitative approach with ethnographic methods, this research tries to trace the history and development of the two types of music, namely through data sources of academic literature, direct observation and interviews with ethno-music cultural actors. To analyzing the transformation process of Gendang Beleq and Kecimol, this research uses Herbet Spencer's theory of cultural evolution and Karl Marx's theory of class conflict.Spencer's theory used to see the development of the culture of the Sasak people, especially the art of music, in the process of its evolution and transformation. Meanwhile, Marx's class theory used to analyze the class struggle between non-aristocratic versusaristocrats group behind the existential contestation of the two types of music.This research found several things: (1) the emergence of Kecimol is a natural cycle in the cultural evolution stage of a society along with social changes and the presence of modernity; (2) Kecimol is an anti-tesa from Gendang Beleq as a form of resistance from the jajarkarang group against the Purwangse Group which is caused by the cultural-economic-political (cost) problem.